THE EFFECT OF CUSTOMER SERVICE QUALITY AND SATISFACTION ON BUSINESS SUCCESS OF ES PUTER BANG BENNY IN SUB DISTRICT KEMUNING SEKIP KEBON SEMAI PALEMBANG - januar, ida (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study examines the effect of service quality and customer satisfaction on the success of the business of ES Puter Bang Benny in Kemuning sub-district, Kebon Semai, Palembang. The purpose of this study was to find out whether service quality and customer satisfaction had an influence on the success of ES Puter Bang Benny Business in Kemuning Subdistrict, Kebon Semai, Palembang. One of the important element and needs attention in the business world is the existence of consumers. Consumers are users of goods or services available. Consumers will definitely look for products or services according to their needs, so they can satisfy themselves. A consumer in deciding the purchase of an item or service, certainly has several considerations. Therefore, in achieving a business that has the potential to increase market share through meeting the level of quality of customer service. Service quality starts from customer needs and ends with satisfaction. perception or impression with the performance of a product and its expectations. Based on multiple linear regression equations obtained results: Y = 2.236+ 0.357X1 + 0.422X2